The role of self-efficacy and mindfulness in driving innovative behaviour among entrepreneurship educators in higher education institutions: a conceptual paper / Hadezah Amit, Rosli Mahmood and Hishamuddin Md. Som - Amit, Hadezah; Mahmood, Rosli; Md. Som, Hishamuddin (UiTM Press, 2024)
This conceptual paper highlights the connection between self-efficacy, mindfulness, and innovative behaviour among entrepreneurship educators in higher education institutions (HEIs). Self-efficacy, as articulated in Bandura’s Social Cognitive Theory, is considered a crucial factor influencing educators’ confidence in adopting and sustaining innovative teaching methodologies. Mindfulness, or present-moment awareness, is identified as a crucial mediator that enhances educators’ capacity to adapt, reflect, and regulate their emotions, hence amplifying the influence of self-efficacy on innovative behaviour. The concept posits that entrepreneurship teachers with elevated self-efficacy and mindfulness are more inclined to exemplify the inventiveness, problemsolving abilities, and adaptability essential for preparing students for the intricacies of the contemporary business environment. The document highlights the practical ramifications of professional development programmes that enhance both self-efficacy and mindfulness, along with the way’s institutions might facilitate educator creativity. Additionally, the framework advises that subsequent empirical research examine the proposed relationships utilising quantitative methodologies, including structural equation modelling (SEM), and explore the influence of contextual factors such as institutional support. This study contributes to the growing literature on the psychological factors influencing innovative behaviour in education, offering insights into how higher education institutions might more effectively equip educators to excel in dynamic teaching environments.